Phenotypic Identification and Antifungal Susceptibility of Two Rhodotorula Species Isolated from Dandruff Samples - Begum, Kohinur; Shahid, Mashmum Shababa; Ferdoush, Sanzida; Nur, Farjahan (Dhaka University Journal of Pharmaceutical Sciences, 2020)
Rhodotorula are environmental yeasts originally considered non-pathogenic in nature. However, over the last three decades, different species of this yeast have established themselves as pathogens in humans, causing systemic infections among the immunocompromised population. In this study, Rhodotorula species were isolated from dandruff samples using selective media by observing colony morphology and color. The isolates were later identified via biochemical tests and microscopic examinations. In addition, the sensitivity of the isolates to the three antifungal agents, namely ketoconazole, nystatin and fluconazole were tested by using the disk diffusion technique. On completion of the tests, only two species of Rhodotorula were identified from 35 dandruff samples and designated as R1 and R3. Both isolates displayed sensitivity towards ketoconazole and nystatin. No antifungal sensitivity was documented against fluconazole. This study gave preliminary indication of the presence of Rhodotorula species in dandruff samples, and its sensitivity towards antifungal agents. Dhaka Univ. J. Pharm. Sci. 19(2): 185-190, 2020 (December)